ADHD Symptoms in Adults and Time Perspectives – Findings From a Czech National Sample - Weissenberger, Simon; Děchtěrenko, Filip; Klicperova-Baker, Martina; Vňuková, Martina; Zimbardo, Phillip; Raboch, Jiří; Anders, Martin; Braaten, Ellen; Ptáček, Radek (Frontiers in Psychology, 2020)
Introduction Attention deficit hyperactivity disorder (ADHD) is one of the most common neurodevelopmental disorders, affecting individuals in all stages of their lives and leading to a variety of negative quality of life outcomes. The disorder is associated with marked differences related to time perception and time perspectives, and this area of research is currently becoming more prominent and gaining ground in showing new aspects of ADHD that were considered secondary (i.e., time perception differences, affective differences). In this study, we looked at ADHD symptoms in adults, correlated lifestyles, and time perspectives as defined by the Zimbardo Time Perspective Inventory (ZTPI). The ZTPI is a useful standardized scale to measure one’s time perspective anchoring in the categories of past positive, past negative, present fatalistic, present hedonistic, and future oriented. This is the first study on adult ADHD and time perspectives conducted in the Czechia. Methodology A national representative sample of Czech adults aged 18–65 was recruited by the STEM/MARK Agency. The individuals were assessed for ADHD symptoms with the Adult ADHD Self-Report Scale (ASRS v.1.1). Furthermore, a demographic and lifestyle questionnaire was administered along with the ZTPI to assess time perspectives. Statistical calculations were conducted to find correlations between ADHD symptoms as assessed by the ASRS and the various categories of the ZTPI. Results ADHD symptoms were found to be positively correlated with the present hedonistic perspective along with the past negative perspective. Gender was a strong factor in both ADHD symptoms, with males being more likely to show symptoms and to have a present hedonistic perspective. In females, the past negative perspective was most prominent. Education and age were negatively correlated with ADHD symptomatology and the present hedonistic perspective also decreased with age unlike the past negative perspective. Other time perspectives such as future orientation was seen in individuals with lower ADHD symptoms and higher levels of educational achievement. Conclusion Researching ADHD symptoms and their connection to time perspectives can increase knowledge of both the disorder and how time perspectives tie into it. We wish to also raise awareness of the possible utility of the ZTPI scale when working with individuals with ADHD.